The larval and early juvenile fishes and the fry gathering activities in Barangays Palaca and Kirayan Sur, Miagao, Iloilo - Balunan, Roie Losaria (College of Fisheries, 2008)
The biodiversity and abundance of fry and early juvenile fishes caught by fry dozer in Brgy. Kirayan Sur and Palaca, Miagao, Iloilo were determined and the activities of individual fry gatherer and the associations of fry collectors in these barangays were described. A total of 7,578 larval early juvenile fishes were collected in Brgy. Kirayan Sur and Brgy. Palaca. There were 19 families identified in which Apogonidae dominated both areas numbers. The Major families found in Kirayan Sur were Apogonidae (90.70%), Chanidae (3.91%), and Tetraodontidae (3.91%). In Brgy. Palaca, the major families found were Apogonidae (72.92%), Chanidae (11.59%), Terapontidae (11.59%), Penaeidae (4.14%), Gobiidae (2.97%), Belonidae (1.28%), and Tetraodontidae (1.16%). The Shanon-Wiener index results were 0.457 in Brgy. Kirayan Sur and 1.088 in Brgy. Palaca while the evenness values were 0.17 and 0.38 respectively. Brgy. Palaca can be considered to have more diverse fish population compared with Brgy. Kirayan Sur. Peaks of fry occurrence during the study were found to be in October 29 to November 7 and November 22, 2007 in Brgy. Kirayan Sur while in Brgy. Palaca, peaks were found to be in November 7 to November 14 and December 9, 2007. Income during peak months rages from PHP750-PHP1250 per month and during lean months, income inly ranges from PHP30-PHP350 per. Fry gathering activities were participated by able family members regardless of gender and educational attainment. The roles of the concessionaires were found to be important in the management and marketing of fry collected in the two Brgys. Fry gathering activities in Brgys. Kirayan Sur and Palaca were found to be declining and this was attributed to low prices of fry and the availability of hatchery produced milkfish and prawn fry.